The internal market of dairy cooperatives: Chances and challenges of global-market - Hasan, Ishak; Abdullah, Razali; Saputra, Jumadil; Putra, Zainal; Chalirafi, Diana Khairani Sofyan, (Opción, 2019)
This study aims to analyze the Internal Market of Dairy Cooperative and to analyze its implications toward the competitiveness to face the integration of ASEAN Market. This survey was conducted in three dairy cooperatives, KPBS Pangalengan, KPSBU Lembang, and KPS Bogor. The sampling technique used in this research was Stratified Random Sampling (STRS). Research results showed that the internal supporting market of cooperative has positive impacts on the competitiveness of Dairy Cooperative in the external market to face global market integration.